Pemanfaatkan Subtitusi Fly Ash dan Bahan Kapur Alam untuk Peningkatan Mutu Paving Block - Abdul Rokhman; Dhani Van Chairi (Jurnal Sipil Krisna, 2022)
Utilization of waste materials as building materials is a solution to reduce waste materials that exist in nature.Fly ash as a waste product from coal combustion contains silica which can be used to increase the compressivestrength of concrete/mortar. Paving Block as a building material made of mortar composition can be increasedits compressive strength by substituting some cement material with fly ash. Fine aggregate material in the formof sand can also be substituted with natural limestone waste material. In this study, paving blocks were madeusing limestone as a substitute for fine aggregate and fly ash as a cement substitute. The ratio of materials formaking paving blocks is 1: 4. For variations of substitution materials, fly ash is used as a cement substitution.The variation of fly ash is 20% and while the limestone waste is used variations of 0%, 10%, 20%, 30% and 40%.The compressive strength test was carried out at the age of 7 days, 14 days, and 28 days. The results of the studyof compressive strength at the age of 7 days obtained a value of 12.24 MPa at a natural limestone substitutionconcentration of 20.7%. For the age of 14 days the compressive strength value is 15.27 MPa with an optimumconcentration of 20.1% at the concentration of natural limestone, while at the age of 28 days the compressivestrength value is 17.11 MPa, with the optimum concentration of natural limestone material being 20. .15%. Theincrease in compressive strength from the optimum mixture to the normal mixture was 28.93%. Based on SNI 03-0691-1996 the paving blocks produced in this study include Quality B.